Reflecting on the Impact of Generative AI for Sustainability Accounting Scholarship - Apostol Oana; Dey Colin; Thomson Ian (Taylor & Francis, 2025)
Our yearly editorial is dedicated to reflections concerning two recent digitalisation-based developments, both of which are currently radically transforming the publishing arena. We begin by considering the rapid emergence of generative Artificial Intelligence (AI) models known as Large Language Models (LLMs), which have already had tremendous effects on academic knowledge production. In this context, we clarify our stance on the use of AI in articles submitted to Social & Environmental Accountability Journal (SEAJ) and reviews conducted for the journal. We then continue by taking a closer look at the proliferation of systematic literature reviews, in their multiple versions, e.g. bibliometric-based reviews, which are submitted to  the journal in increasing numbers. We use this editorial to revisit our editorial policy and outline the kind of submissions welcomed at SEAJ.